Análise térmica de um coletor solar composto de cavidades V para aquecimento de água - Michel Fabio de Souza Moreira (2009)
The solar water heating is carried through, in Brazil, by means of solar heaters compound for collectors flat plate of the type plate-and-pipes, devices that operate in stationary position and they do not require tracking of the sun. A compound collector for some formed V-trough concentrators can be an alternative to the conventional solar collectors flat plate. This compound collector for V-trough is considered, each one, for side-walls which are specularly reflecting surfaces associates in V (equivalent to a triangular gutter). Next to the vertex to each V-trough concentrators an absorber tube is fixed, for flow of the fluid to be heated. Interconnection of the absorbers tubes forms a similar tubular network existing in solar collectors of the type the plate and pipe. V-trough concentrators with the absorbers tubes are made use in series in the interior a prismatic box, which have one of its faces consisting by a glass covering and directed toward incidence of the solar radiation. An analysis of thermal performance of these devices operating stationary and without trackingof the sun is researched. A mathematical model for the computational simulation of the optical and thermal performance of these concentrative devices is elaborated, whose implementation was carried through software EES (Engineering Equation Solver). The efficiency optics of V-trough concentrators with cylindrical absorbers is calculated from theadaptation of the methodology used for Fraidenraich (1994), proposal for Hollands (1971) for V-trough cavities with plain absorbers. The thermal analysis of the considered collector was based on the applied methodology the CPC for Hsieh (1981) and Leão (1989). Relativeresults to the thermal performance of V-trough concentrators suggest that these configurations are not competitive, technique and economically, with the conventional plain collectors. Although some geometric configurations presented next thermal efficiencies to the conventional plain collectors, its raised unitary costs, however, make impracticable, at a first moment, for the domestic water heating.